Mathematical modeling of subdiffusion impedance in multilayer nanostructures - Kostrobij, P. P.; Grygorchak, I. I.; Ivaschyshyn, F. O.; Markovych, B. M.; Viznovych, O. V.; Tokarchuk, M. V. (Publishing House of Lviv Polytechnic National University, 2015)
The model of impedance subdiffusion based on the Cattaneo equation in fractional derivatives in applications to multilayer nanostructures is considered. Nyquist diagrams with changes of the parameter (time for which the flow is delayed with respect to the concentration gradient) and the subdiffusion coefficient D are calculated. Розглянуто модель субдифузiйного iмпедансу на основi рiвняння Кеттано у дробових похiдних у застосуваннi до мультишарових наноструктур. Розраховано дiаграми Найквiста iз змiною параметрiв (час, на який потiк затримується вiдносно градiєнта концентрацiї) та субдифузiйного коефiцiєнта D.
Математичне моделювання субдифузiйного iмпедансу в мультишарових наноструктурах
Keywords: fractional derivative; Cattaneo equation; Nyquist diagram; impedance; дробова похiдна; рiвняння Кеттано; дiаграма Найквiста; iмпеданс